2015
DOI: 10.1089/brain.2014.0230
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Repertoire of Intrinsic Brain States Is Reduced in Propofol-Induced Unconsciousness

Abstract: The richness of conscious experience is thought to scale with the size of the repertoire of causal brain states, and it may be diminished in anesthesia. We estimated the state repertoire from dynamic analysis of intrinsic functional brain networks in conscious sedated and unconscious anesthetized rats. Functional resonance images were obtained from 30-min whole-brain resting-state blood oxygen level-dependent (BOLD) signals at propofol infusion rates of 20 and 40 mg/kg/h, intravenously. Dynamic brain networks … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

20
123
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 142 publications
(144 citation statements)
references
References 113 publications
20
123
0
1
Order By: Relevance
“…6A). This result is consistent with the notion that the awake state is associated with a richer functional repertoire (Barttfeld et al, Hudetz et al, 2015). The averaged absolute connectivity strength as a function of physical distance between ROIs was shown in Figure 6B for all three dRSFC patterns.…”
Section: Fig 4 (A)supporting
confidence: 90%
See 1 more Smart Citation
“…6A). This result is consistent with the notion that the awake state is associated with a richer functional repertoire (Barttfeld et al, Hudetz et al, 2015). The averaged absolute connectivity strength as a function of physical distance between ROIs was shown in Figure 6B for all three dRSFC patterns.…”
Section: Fig 4 (A)supporting
confidence: 90%
“…These methods have made it feasible to investigate the brain network dynamics at different states of consciousness (Barttfeld et al, 2015;Liang et al, 2015a). Indeed, with these approaches, it has been shown that the dynamic properties of brain network connectivity may constitute key characteristics of consciousness (Barttfeld et al, 2015;Breshears et al, 2010;Hudetz et al, 2015).…”
mentioning
confidence: 99%
“…Such simulations have established that, for low coupling strength between brain areasa configuration that resembles the sedated condition-spontaneous neuronal activity is still present but mostly traces the fixed network defined by structural connectivity, and as a result, only a single stable spontaneous connectivity pattern occurs (16,17). As the coupling strength increases, a qualitative change in the dynamics occurs: instead of having a single stable state, the system becomes multistable; functional activity spontaneously breaks down into a diversity of states that is sequentially explored in a stochastic manner (16,21,23,37,38). It has been argued that the brain operates precisely at the edge of this dynamical change-or critical state (39)-in which the system is maximally sensitive to external stimulation.…”
Section: Discussionmentioning
confidence: 99%
“…simulations of resting state brain activity (16,(21)(22)(23)(24), is that signatures of the conscious state lie in the dynamics of spontaneous brain activity. When averaged across a long time period, functional brain activity may appear similar in wakefulness and anesthesia (10,11,25), due to the existence of a backbone anatomical connectivity.…”
Section: Significancementioning
confidence: 99%
See 1 more Smart Citation